Diagnosis of Joint Affection in Camels by Studies on Synovial Fluid which Give the Degree of Affections & Response to Treatment - Hegazi, Ashraf Abdel-Hamid; Elhmri, Khaled M.A. Hussin (Al-Mukhtar Journal of Sciences, 2008)
Camels have great economic importance for their high working capacity and sources for human consumption as regards meat , milk and wool production .studies of synovial fluid in joint help in diagnosis of joint affections and determining the reasonable line of treatment of this joint .Study in detail the diagnostic value of analysis of the synovial fluid in certain Joints in normal and diseased camels . carpal joint Radio-ulnar-carpal Intercarpal Carpo-metacarpal Metacarpophalangeal Tibiotarsal Metatarso-phalangeal The total numbers of synovial fluid samples are 82 samples (60 normal synovial samples and 22 affected synovial samples) with the reference to the physical (Gross appearance , reaction , volume and mucinous precipitation quality) , cytological (total and differential leucocytic counts) and chemical Features (al.p.,L.D.H,Got and Gpt , sugar concentration , total protein and uric acid level ) on the synovial fluid collected by Arthrocentesis from these joints In addition to the radiographic studies of these joints capsule extensions , via positive and negative contrast arthrography .